Genetic variability in E6, E7, and L1 genes of human papillomavirus genotype 52 from Southwest China - Zhang, Yiwen; Cao, Man; Wang, Mengting; Ding, Xianping; Jing, Yaling; Chen, Zuyi; Ma, Tengjiao; Chen, Honghan (Gene, 2016)
Human papillomavirus (HPV) is the major causative agent of cervical cancer, which accounts for the second highest cancer burden in women worldwide. HPV-52, the prevalent subtype in Asia, especially in southwest China, was analyzed in this study. To analyze polymorphisms, intratypic variants, and genetic variability in the E6–E7 (n=26) and L1 (n=53) genes of HPV-52, these genes were sequenced and the sequences were submitted to GenBank. Phylogenetic trees were constructed using the neighbor-joining and Kimura 2-parameters methods, followed by analysis of the diversity of secondary structure. Finally, we estimated the selection pressures acting on the E6–E7 and L1 genes. Fifty-one novel variants of HPV-52 L1, and two novel variants of HPV-52 E6–E7 were identified in this study. Thirty single nucleotide changes were observed in HPV-52 E6–E7 sequences with 19/30 non-synonymous mutations and 11/30 synonymous mutations (five in the alpha helix and five in the beta sheet). Fifty-five single nucleotide changes were observed in HPV-52 L1 sequences with 17/55 non-synonymous mutations (seven in the alpha helix and fourteen in the beta sheet) and 38/55 synonymous mutations. Selective pressure analysis predicted that most of these mutations reflect positive selection. Identifying new variants in HPV-52 may inform the rational design of new vaccines specifically for women in southwest China. Knowledge of genetic variation in HPV may be useful as an epidemiologic correlate of cervical cancer risk, or may even provide critical information for developing diagnostic probes. •HPV-52 E6–E7 and L1 genes were sequenced to identify genetic variants.•Amino-acid mutations related to secondary structure may affect protein function.•Neighbor-joining trees were constructed for E6–E7 and L1 gene sequences.•Selection pressures acting on E6–E7 and L1 genes were estimated.•Positive selection was identified as a driver of genetic changes.